Dispatcher-assisted cardiopulmonary resuscitation: Differential effects of landline, Mobile, and transferred calls. (1st January 2020) - Huang, Shuo Kuen; Chen, Chih-Yu; Shih, Hong-Mo; Weng, Shao-Jen; Liu, Shih-Chia; Huang, Fen-Wei; Su, Chi-Yueh; Chang, Shih-Hsien
Abstract: Background: Dispatcher-assisted cardiopulmonary resuscitation (DACPR) could improve the survival rate of out-of-hospital cardiac arrest (OHCA). However, the efficiency of DACPR varies. Our study compared the effectiveness of DACPR instructed via landline calls, mobile calls, and landline calls transferred to mobiles. Method: This prospective cohort study enrolled patients with OHCA between 1 July 2017 and 30 November 2018 in Taichung. Patients were divided into a mobile group and a landline group according to device used to call emergency medical services (EMS). The landline group was subdivided according to whether the call was transferred to a mobile. We compared the DACPR rate and call to chest compression time between groups. Results: The study comprised 2404 cases after exclusion: 934 cases of DACPR via mobile and 1470 via landline. In the mobile group, DACPR rate (54% vs. 47.5%, P < 0.001) was higher and call to chest compression time (median: 156 s vs. 174 s P < 0.001) was shorter than in the landline group. In the transferred group, DACPR rate (72.7% vs. 28.8%, P < 0.001) was higher than in the non-transferred group, but no difference was observed in call to chest compression time (median: 173 s vs. 177 s, P = 0.69). Conclusion: According to this city-based prospective clinical study, communication over mobiles resulted in higher DACPR rate and shorter call to chest compression time than that over landlines. Transferring calls from a landline to a mobile could increase the DACPR rate without delaying the initiation of chest compression.